Improving the Quality of Hospital Services Through the Integration of Servqual, Kano, and Two Iterations of Quality Function Deployment (QFD) - Rafidah, Ghina; Hendayani, Ratih; Hidayah, Riski Taufik (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose – This research focuses on the problem of decreasing the number of private hospital visits, one of the causes of which is patient dissatisfaction with the healthcare services provided. This research aims to design recommendations for improving the quality of a hospital's health services based on the perceived needs of patients so that it is hoped that patient satisfaction can be achieved well. Methodology/approach – The literature review defines service quality and patient requirements in this research. Servqual and Kano questionnaires are used in this research, with 150 patients as respondents. After the quantitative data has been obtained and analyzed, the next step is to collect qualitative data by conducting interviews with health service management experts. By using QFD analysis, the relations between patient requirements and service characteristics are obtained. Targeted health service criteria will be chosen to be used as recommendations to improve hospital services. Findings – Some patient requirements are not optimally fulfilled by the hospital. Service characteristics and service critical parts are prioritized for the recommendation in improving the hospital health services. Novelty/value – The research combines scientific disciplines marketing, namely Service Quality (Servqual) and scientific disciplines operations management, namely Kano and Quality Function Deployment (QFD) first iteration (House of Quality) and second iteration (Part Deployment), with the hospital’s health service as the research object. The integration can be used in other service companies, especially in health services.